Robustness of the minimal control synthesis algorithm with minimal phase plant dynamics of unknown order but known relative degree - Hodgson, S. P.; Stoten, D. P. (International journal of control, 1998)
This paper presents proofs of stability and robustness of the minimal control synthesis (MCS) and decentralized minimal control synthesis (DMCS) algorithms applied to minimal phase plant of known relative degree but unknown order, using the concept of system passivity. The theoretical stability result is supported by a comparative implementation study.